Characterization of Mucilages from Abelmoschus Manihot Linn., Amaranthus Spinosus Linn. and Talinum Triangulare (Jacq.) Willd. Leaves for Pharmaceutical Excipient Application - Ang, Aileen May Gabule; Raman, Inocencio Caňete (Asian Journal of Biological and Life Sciences, 2019)
Introduction:The edible leaves ofAbelmoschus manihotLinn.,Amaranthus spinosusLinn. andTalinum triangulare(Jacq.) Willd. are exhibiting mucilaginous features and are utilized in making soupy dishes. However, the utilization of the said plant species as sources of mucilages for pharmaceutical excipient application has not yet been reported in literatures.Objectives:The study aimed to extract and partially characterize mucilages from the leaves ofA. manihot, A. spinosusandT. triangulare. for potential pharmaceutical excipient application.Materials and Methods:Mucilages were extracted from the leaves ofA. manihot, A. spinosusandT. triangulare. Preliminary qualitative tests as well as determination of the physico-chemical properties, i.e. pH, solubility, swelling index, loss on drying, total sugar content and total uronic acid content, were conducted on the extracted mucilages. Identification of functional groups were also carried out through Fourier Transform Infrared (FTIR) spectroscopy.Results and Discussion:Results of the qualitative tests showed detection of carbohydrates, polysaccharides and mucilages among the mucilages extracted fromA. manihot, A. spinosusandT. triangulare.The pH values of the extracted mucilage were nearly neutral indicating that they can be less irritating to the gastrointestinal tract when utilize for tablet formulations. Data obtained for the physico-chemical properties showed that mucilages ofA. manihotgave statistically different values as compared to the mucilages derived fromA. spinosusandT. triangulare. A. manihotmucilage exhibited significantly higher swelling index (357.78%) and total sugar content (273.65 mg glucose/g extract) and significantly lower loss on drying (10.72%) and total uronic acid content (105.20 mg glucuronic acid/g extract) than the other mucilages from A. spinosus and T. triangulare. Furthermore, FTIR spectral analysis showed typical peaks and characteristic bands of mucilage.Conclusion:A. manihotmucilage is promising for utilization as pharmaceutical excipient. However, further analysis is recommended.
Keywords: Abelmoschus manihot; Amaranthus spinosus; Mucilages; Talinum triangulare